Prospective evaluation of causes of infertility at a tertiary care hospital - Soni, Monica; Kumari, Santosh (International Journal of Research in Medical Sciences, 2018)
Background: Infertility is defined as the failure to achieve a clinical pregnancy after 12 months or more of regular unprotected sexual intercourse. Worldwide, its prevalence is approximately 8-12%. There are numerous factors such as anatomical, physiological, genetic, environmental and acquired factors that cause infertility. The aim of the present study was to determine the causes and clinical pattern of infertility in infertile couples in North West India. Methods: It was a hospital based observational study carried out on 211 infertile couples in reproductive age group attending infertility clinic of Sardar Patel Medical College and associated PBM Hospital, Bikaner, Rajasthan between September 2016-February 2017. Collection of data was performed by means of a specifically designed questionnaire, which apart from the demographic data also included questions concerning the causes of infertility. Cases of infertility diagnosed after detailed history, clinical examinations and laboratory tests were included. Results: Out of 211 infertile couples, female factor was predominant in 60.18%, male factor in 15.16%, unexplained in 15.16% while a combination of both factors was seen in 9.47% cases in our study. 33.17% women had ovulatory dysfunction diagnosed by menstrual history and ultrasonography. Tubal block was observed in 9.47% infertile women. 6.63% women had hypothyroidism and 1.89% infertile women were diagnosed to have endometriosis. Husband semen analysis was also done to assess male factor. Nearly 5.21% of their male partners suffered from oligospermia, 4.73% had azoospermia and oligoasthenospermia was observed in 3.79% male partners. Conclusions: Predominant cause of infertility can be reported in male or female partner or both so, either partner should be counselled and investigated properly. Our study reports a predominance of female factors as a cause of female infertility but male factors also accounted for a significant number of cases.